2009
DOI: 10.4314/eamj.v77i5.46629
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoma of the head and neck at Kenyatta National Hospital

Abstract: Objective: To determine the pattern of occurrence of sarcomas afflicting the neck and craniofacial region. Design: A retrospective study (1982-1991).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 16 publications
2
11
3
Order By: Relevance
“…25 Osteosarcoma was the most frequently diagnosed HTS, and this is consistent with data from other parts of Africa. 10,18,20 Our study found no sex preference, with M:F of 1:1 in contrary to the findings of Guevara-Canales et al 12 and Kamau et al 18 that…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…25 Osteosarcoma was the most frequently diagnosed HTS, and this is consistent with data from other parts of Africa. 10,18,20 Our study found no sex preference, with M:F of 1:1 in contrary to the findings of Guevara-Canales et al 12 and Kamau et al 18 that…”
Section: Discussioncontrasting
confidence: 81%
“…19,30 Fibrosarcoma is a malignant tumor whose occurrence in the head and neck is rare, accounting for less than 5% of fibrosarcomas of all sites. 20 In this series, the incidence of fibrosarcomas was 4.5%, with a mean age of occurrence being 40.7 years, having slightest higher prevalence among male patients. Some studies from different parts of the world show similar male predominance, 12,20 others report of equal predilection, 13,19 while Kamau et al 18 found a higher prevalence in females.…”
mentioning
confidence: 53%
See 3 more Smart Citations